2016
DOI: 10.1007/s13593-016-0399-1
|View full text |Cite
|
Sign up to set email alerts
|

Chestnut wood extract in boar diet reduces intestinal skatole production, a boar taint compound

Abstract: Abandoning traditional practice of piglet castration will impact the pigmeat sector. As a consequence, there is a need for research aiming at reducing boar taint caused by androstenone and skatole. Skatole is metabolized by cytochrome P450 enzymes (CYP450) in the liver. Skatole hepatic clearance is believed to be hindered by androstenone. Diet ingredients may modify skatole metabolism. Therefore, we tested the effect of hydrolysable tannins. We fed 51 young boars with 1-3 % chestnut wood extract as supplementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…These results suggested that hydrolysable tannins can be used to reduce skatole levels in pigs by induction of skatole‐metabolizing enzymes. However, later studies on dietary supplementation with hydrolysable tannins to conventional pig breeds did not show any effect on CYP2A19 and CYP2E1 mRNA expression . These contradictory results might indicate breed‐related differences in the response to dietary tannins.…”
Section: Dietary Regulation Of Cyp2a19 and Cyp2e1mentioning
confidence: 95%
See 3 more Smart Citations
“…These results suggested that hydrolysable tannins can be used to reduce skatole levels in pigs by induction of skatole‐metabolizing enzymes. However, later studies on dietary supplementation with hydrolysable tannins to conventional pig breeds did not show any effect on CYP2A19 and CYP2E1 mRNA expression . These contradictory results might indicate breed‐related differences in the response to dietary tannins.…”
Section: Dietary Regulation Of Cyp2a19 and Cyp2e1mentioning
confidence: 95%
“…Often, CYP2E1 protein expression and corresponding activity are regulated at the post‐transcriptional level . Thus, changes in porcine CYP2E1 mRNA expression are not always reflected in corresponding changes in CYP2E1 protein expression and activity . Early studies have shown that acetone and ethanol treatment induces CYP2E1 protein expression in rats because of stabilisation of the protein by inhibiting its degradation .…”
Section: Translational and Post‐translational Regulation Of Cyp2a19 Amentioning
confidence: 99%
See 2 more Smart Citations
“…It is found that the oral charcoal adsorbent AST-120 binds indole in the intestinal lumen, and reduces the blood plasma indole sulfate levels, in turn decreasing kidney damage and atherosclerosis-related kidney injuries [ 61 ]. Another important product of tryptophan metabolized by mammalian gut microbiota is skatole, which has been proven to cause pulmonary edema in sheep, goats, and some strains of mice [ 62 ]. It selectively targets club cells, which are the key sites of cytochrome P450 enzymes in the lungs [ 62 ].…”
Section: Dietary Amino Acidsmentioning
confidence: 99%